Analysis and Design of Jobs for Control of Cumulative Trauma Disorders: Plastic Forks/Spoons Packing Job - Law, P.L; Ng, Chee Khoon; Ha, How Ung; Lau, Hieng Ho (The Institution of Engineers, Malaysia, 2005)
Cumulative trauma disorders caused by repetitive hand and arm movements were studied in this paper for a plastic forks/spoons packing job. The job was categorised into several work elements associated with the trunk, hand and arm motions. The number of motions were then counted for each eight-hour shift. It was found that the worker has to move the right hand 45,211 times and left hand 45,931 times for a working shift. In some of the motions, the worker has to twist the trunk. This relatively high number of motions is due to the current positioning of equipment and tools. With some considerations on the positioning and orientation such as distances and heights, the repetitive motions of the hands and arms can be significantly reduced, hence minimising the risk factors associated with cumulative trauma disorders.